2011
DOI: 10.1155/2011/379173
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Clinical Trial of Niacinamide 4% versus Hydroquinone 4% in the Treatment of Melasma

Abstract: Background. Multiple modalities have been used in the treatment of melasma with variable success. Niacinamide has anti-inflammatory properties and is able to decrease the transfer of melanosomes. Objective. To evaluate the therapeutic effect of topical niacinamide versus hydroquinone (HQ) in melasma patients. Patients and Methods. Twenty-seven melasma patients were randomized to receive for eight weeks 4% niacinamide cream on one side of the face, and 4% HQ cream on the other. Sunscreen was applied along the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 14 publications
7
99
2
6
Order By: Relevance
“…Skin color of UVB-induced pigmentation was brighter in glabridin group than control group, and UVB-induced erythema was reduced compared to control in vivo [20]. In another study, the value of a * was reported to have no significant difference even though the values of L * changed considerably [11]. So, we suggest that the combination of niacinamide and G. glabra provides the synergy on improvement of brightness and redness, and the difference with the previous study comes from different study conditions such as concentration, skin type and comparison method.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Skin color of UVB-induced pigmentation was brighter in glabridin group than control group, and UVB-induced erythema was reduced compared to control in vivo [20]. In another study, the value of a * was reported to have no significant difference even though the values of L * changed considerably [11]. So, we suggest that the combination of niacinamide and G. glabra provides the synergy on improvement of brightness and redness, and the difference with the previous study comes from different study conditions such as concentration, skin type and comparison method.…”
Section: Discussionmentioning
confidence: 92%
“…A few agents include niacinamide and plant extracts has various effects on skin [11,12]. Previously, a study has shown that niacinamide inhibits melanosome transfer, suggesting that it reduces melasma [12].…”
mentioning
confidence: 99%
“…Niacinamide reduced the mast cell infiltrate and showed improvement of solar elastosis in melasma skin. Side effects were present in 18% with niacinamide versus 29% with hydroquinone [41].…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%
“…It also increases biosynthesis of ceramides, as well as other stratum corneum lipids with enhanced epidermal permeability barrier function. Moreover, it has antiaging effects [41].…”
Section: Other Botanicals As Potential Bleaching Agentsmentioning
confidence: 99%
“…Hakozaki et al demonstrated in vitro that niacinamide exhibited effective skin-lightening activity by inhibiting the transfer of melanosomes to adjacent keratinocytes by 35%-68% [18,19] . In a clinical study, Navarrete-Solís et al reported that 8 weeks of treatment with 4% niacinamide cream showed good to excellent improvement in 44% of patients with melasma, compared to 55% from a 4% hydroquinone cream treatment [20] .…”
Section: Niacinamide (Vitamin B 3 )mentioning
confidence: 99%